Pentagon fraud dimensions effects on students’ academic dishonesty in online-based learning at vocational high schools - Jatmika, Surya; Karima, Mutiara; Pertiwi, Puspita; Martama, Happy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Academic dishonesty is one of the fraud behaviours in education institutions caused by several factors. This study aimed to determine the influences of the pentagon fraud dimensions (pressure, opportunity, rationalizsation, ability, and arrogance) on academic dishonesty in online Accounting learning at SMK Business and Management in Sukoharjo Regency. This research applied a quantitative approach with a causal-comparative research design. The sample included randomly selected 115 Grade XI students of Accounting and Financial Institutions at SMK Negeri 6 Sukoharjo and SMK Muhammadiyah Watukelir Sukoharjo. The data were collected using questionnaires and analysed using nonparametric statistics with the Kruskal-Wallis test. Based on the results of the Kruskal-Wallis test, the opportunity variable has an Asymp. Sig. value of 0.001, rationalisation of 0.043, ability of 0.006, and arrogance of 0.002. These values ​​are smaller than the significance level of 0.05, so Ha is accepted. While the pressure value of 0.573 is greater than 0.05. The results of the study indicate that academic dishonesty in online Accounting learning at SMK Bisnis dan Manajemen Sukoharjo Regency, when viewed from the Fraud Pentagon dimension, is influenced by the opportunity, rationalisation, ability, and arrogance variables, but is not influenced by the pressure variable. In an effort to lower academic dishonesty, schools should implement stronger controls to minimise the chances of cheating, provide ethics training to combat rationalisation, enhance students' capabilities through study aid, and foster a culture of integrity in order to surmount arrogance.